PENDIDIKAN KEWARGANEGARAAN DALAM MEMPERKOKOH NASIONALISME DI ERA GLOBALISASI - Yuliandari, Erna (PKn Progresif, 2008)
This article aims to examine the impact of globalization to nation-state. Propertiy and advantages brought about by globalization , however is not equal in many country. This article argues that in the development country the impact of globalization to nation state with nationalism Civic Education have very strategic role in tighten nationalism